Does global value chain engagement improve firms' wages: Evidence from China. (31st May 2019) - Lu, Yue; Lu, Yunlong; Xie, Rui; Yu, Xiao
Abstract: Better understanding of the effect of the global value chain (GVC) on wages is a key issue for determining welfare gains from engagement in international integration. We study whether and how China's engagement in the GVC enhances firms' wage by using firm‐level and customs transaction‐level data covering the period 2000–06 with the methods of propensity score matching (PSM), difference in differences (DID) and generalised propensity score (GPS). The empirical results show that first, GVC engagement can improve firms' wage. Second, the improvement effect is more prominent in capital‐intensive and foreign‐invested enterprises. Third, the degree of embedment in the GVC shows a U‐shaped relationship with wages (the marginal improvement changes from decreasing to increasing). Finally, by analysing the mechanism, we find that participation in the GVC ultimately improves the overall wage level of enterprises through the productivity effect and the reallocation effect of labour demand.